2006
DOI: 10.1038/sj.embor.7400615
|View full text |Cite
|
Sign up to set email alerts
|

Skin human papillomavirus type 38 alters p53 functions by accumulation of ΔNp73

Abstract: The E6 and E7 of the cutaneous human papillomavirus (HPV) type 38 immortalize primary human keratinocytes, an event normally associated with the inactivation of pathways controlled by the tumour suppressor p53. Here, we show for the first time that HPV38 alters p53 functions. Expression of HPV38 E6 and E7 in human keratinocytes or in the skin of transgenic mice induces stabilization of wild-type p53. This selectively activates the transcription of DNp73, an isoform of the p53-related protein p73, which in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
135
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(150 citation statements)
references
References 16 publications
11
135
1
Order By: Relevance
“…We therefore determined whether similar events occurred in the mouse model. DNp73 expression levels were analysed by reverse transcriptase-PCR in HPV38 E6/E7 Tg mice in the presence or absence of p53 as previously described (Accardi et al, 2006). In agreement with the in vitro data, we observed that p53 À/À HPV38 E6/E7 Tg mice did not express DNp73 (Figure 1a).…”
supporting
confidence: 76%
See 4 more Smart Citations
“…We therefore determined whether similar events occurred in the mouse model. DNp73 expression levels were analysed by reverse transcriptase-PCR in HPV38 E6/E7 Tg mice in the presence or absence of p53 as previously described (Accardi et al, 2006). In agreement with the in vitro data, we observed that p53 À/À HPV38 E6/E7 Tg mice did not express DNp73 (Figure 1a).…”
supporting
confidence: 76%
“…Since downregulation of DNp73 by antisense oligonucleotide in HPV38 E6/E7 keratinocytes led to a restoration of p53 transcriptional functions (Accardi et al, 2006), we next determined whether similar events can occur in HPV38 E6/E7 Tg mice lacking DNp73. HPV38 E6/E7 Tg mice were crossed with p73 À/À mice, which were previously generated by replacing the exons 5 and 6, leading to deficiency of all p73 isoforms (Yang et al, 2000).…”
mentioning
confidence: 99%
See 3 more Smart Citations